Religious studies of cannibalism - Titov, Serhiy (Skhid, 2017)
The article provides a comprehensive review of latest religious studies research into the phenomenon of cannibalism. All materials are supported with real-world modern examples, based on media reports and findings of primatology and anthropology. In attempt of revealing religious aspect of cannibalism the article presents interesting findings from the author's own anthropological experience in Western Africa. Using classification schemes of the subject, mainly developed and represented in the field of anthropology, the author compares similar aspects in both approaches of anthropology and religious studies. Having applied a variety of classification schemes and methods, the author demonstrates a number of interesting findings. Study analyzes religious meaning of cannibalism that overlaps with social and political significance of consuming enemies to mark one's dominance and superiority or consuming a dead relative to express love, or in attempt to distance the spirit of the deceased from the world of the living, or to acquire physical or spiritual qualities contained in the corpse. Thus sacrifice, the aggressive destruction of enemies, and the devoted incorporation of anxious destruction of a loved one's body are all facets of cannibalism that may be presented in different cultural context. Despite the common assumptions that cannibalism has been seen as characteristic of primitive communities the article analyzes variety of cannibalistic practices in modern complex society. The article contains some fundamental assumptions supporting the belief that traditional approach contributes to seemingly counter-productive common attitude to the phenomenon of cannibalism and prevents academic minds from deeper understanding of it. The author pays particular attention to the aspect of presence or absence of religious beliefs behind all the mentioned acts.